2019
DOI: 10.3233/ies-192150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soft and semi-rigid ankle braces on kinematic and kinetic changes of the knee and ankle joints after forward and lateral drop landing in healthy young women

Abstract: BACKGROUND: Ankle braces are commonly used to protect ankle joints from a sprain by restricting inversion. However, the difference between a soft brace (SB) and a semi-rigid brace (SRB) regarding kinematic and kinetic changes of the lower limb joints after forward and lateral drop landing is unknown. OBJECTIVE: The aim of this study was to evaluate the effect of SB and SRB, on kinematic and kinetic changes after each drop landing in healthy young women. METHODS: Ten female adults were assessed for one leg whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The indices calculated included the anterior-posterior stability index (APSI), mediolateral stability index (MLSI), and vertical stability index (VSI), which reflect the stability in the anterior-posterior, mediolateral and vertical directions, respectively. The dynamic postural stability index (DPSI) is an extensive evaluation computed by amalgamating the ground reaction force in all three directions, reflecting the comprehensive stability of the human body [ 21 ]. Higher APSI, MLSI, VSI and DPSI values correspond to decreased dynamic stability, whereas lower values indicate enhanced stability [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The indices calculated included the anterior-posterior stability index (APSI), mediolateral stability index (MLSI), and vertical stability index (VSI), which reflect the stability in the anterior-posterior, mediolateral and vertical directions, respectively. The dynamic postural stability index (DPSI) is an extensive evaluation computed by amalgamating the ground reaction force in all three directions, reflecting the comprehensive stability of the human body [ 21 ]. Higher APSI, MLSI, VSI and DPSI values correspond to decreased dynamic stability, whereas lower values indicate enhanced stability [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, on the other hand, the ankle brace could also increase the ground reaction force in the half-squat parachuting landing ( Niu et al, 2011 ), which was the negative effect of the ankle brace protection. In the drop landing, the joint moment of the ankle was not significantly influenced with the ankle brace ( Zhang et al, 2012 ; Maeda et al, 2019 ). The joint energy absorption of the ankle was decreased by the ankle brace ( Gardner et al, 2012 ).…”
Section: Introductionmentioning
confidence: 96%
“…In our previous study, the multi-joint protection for the hip, knee, and ankle in the half-squat parachuting landing was found to be provided by a knee brace, which was another type of protective device (Jiang et al, 2020). For motion of the knee and hip in the drop landing, it was reported that the angular displacement of the knee and the hip was not significantly influenced by the ankle brace in the previous study (Cordova et al, 2010;Agres et al, 2019;Maeda et al, 2019). It was meaningful for protecting the lower-extremity joints if an ankle brace could provide the multi-joint protection for the hip, knee, and ankle.…”
Section: Introductionmentioning
confidence: 97%
“…Meta-analyses have shown that ankle orthotics is effective for the primary and secondary prevention of acute ankle injuries among athletes [ 1 ]. Nevertheless, ankle orthotics may have a negative impact on athlete performance in activities such as sprinting [ 2 ], cutting [ 3 ], jump landing [ 4 , 5 ], and vertical jumping [ 2 ]. Furthermore, there is a consensus that ankle orthotics reduces the vertical jump height [ 6 12 ].…”
Section: Introductionmentioning
confidence: 99%